Optimizing Centralized Financial Management for MSMEs in the Mbulak Wilkel Tourism Area of Bantul with the Approaches of (Tri-N) Niteni, Nirokke, Nambahi, and Tri Pantangan - Suciani, Leni; Pitaloka, Dyah Ayu; Sari, Serly Faisa Nur Fatika; Rifaldi, Rifaldi; Setiawan, Miko; Sari, Pristin Prima (PT Inovasi Pratama Internasional, 2024)
This study aims to optimize centralized financial management for MSMEs in the Mbulak Wilkel tourism area of Bantul through a local wisdom-based approach, specifically the concepts of